Success factors and barriers to implementing lean in the printing industry: A case study and theoretical framework. Issue 4 (2nd May 2017) - Ainul Azyan, Zuliyanti Hanizan; Pulakanam, Venkateswarlu; Pons, Dirk
Abstract : Purpose: Lean principles are applied in manufacturing and service industries extensively, but its successful application in the printing industry has been poor. The purpose of this paper is to explore the factors that impede the uptake of lean in the printing industry. Design/methodology/approach: Qualitative case study research methods were used to explore success factors and barriers to implementing lean in printing by interviewing two managers and three employees at each of two printing firms that had implemented lean to different degrees. Findings: A number of critical success factors and barriers to implementing lean are identified. Success factors include practitioners' understanding of lean philosophy, principles and methods, management leadership and commitment, upfront training in lean and effective communication. Originality/value: The work contributes to empirical research on implementing lean in the printing industry. This research identified critical success and failure factors in implementing lean in this industry. Management knowledge, commitment, and support emerged as key factors. A theoretical framework is provided that proposes relationships of causality for the successful implementation of lean in this industry.